Healthy and Safe Internet Psychoeducation (INSAN) to Increase Parent’s Supervision on Using Internet for Children in Yogyakarta - Noviyanti, Devi; Rachmawati, Mira Aliza (Universitas Muhammadiyah Surakarta, 2019)
This study aims to determine the effect of healthy and safe internet psychoeducation (INSAN) to increase parental supervision of internet use in children. The subjects consisted of 7 subjects, the experimental group consisted of 4 subjects and the control group consisted of 3 subjects. The design of this study used two group pretest-posttest designs. This data was analyzed by using quantitatively of Wilcoxon Signed Ranks Test. The researcher also uses observation and interview methods to obtain qualitative data as a complement to the data. The method of parent’s supervision was measured by using methods in parents supervising their children ‘s use of internet-scale (Wong, 2010) which consisted of 17 items. The results of the Wilcoxon test showed (p> 0.05), so it could be concluded there is no effect of psychoeducation of INSAN on increasing parent’s supervision.